AP Librae: The Extended Jet as the Source of VHE Emission? - Michael Zacharias; Stefan J. Wagner (Galaxies, 2016)
The LBL AP Librae has been detected in the TeV gamma-ray range, which is unexpected for this kind of blazar. The broad-band SED cannot be explained by a one-zone model, and especially fails in the TeV domain. An extended jet has been detected on arcsec scales both in radio and X-ray frequencies. The spectral index of the X-ray band indicates an inverse Compton origin. Using an IC/CMB model, the TeV emission can be successfully modeled as originating in the extended jet. Several arguments in favor of this model, as well as observational tests, will be presented. The observations suggest that acceleration of particles to very high energies is still efficient at large distances from the core.